(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2023)
After a few preliminary remarks on Philippe Gauthier’s conception of the relationship between law and history, we turn more specifically to chapter 7 of the Symbola, devoted to isopoliteia, to assess the current relevance of the author’s hypotheses on this granting and sometimes exchange of citizenship between cities and/or koina. Since the aim of the book is to study all forms of judicial protection for passing foreigners, the question is whether isopoliteia is one of them. The author proceeds, as he does elsewhere, by analysing cases, in particular the agreement between Pontic Olbia and Miletus (Miletus I.3, 136) as well as the whole dossier linking the Cretan Epikles of Waxos with the Aetolians (Syll3, 622A and B). Three guidelines are followed here, allowing the work to be placed in a historiographical perspective with reference to the later books by W. Gawantka (1975) and S. Saba (2020): the use of the term isopoliteia in Greek and the contours of isopolity as constructed by modern historians; the definition of the term and the content to be given to it; finally, the question of the legal and judicial scope of isopoliteia. On this last point, Gauthier’s conclusion still seems convincing, since the decrees and agreements of isopoliteia provide their beneficiaries with real protection. On the other hand, in line with recent work, the present article is more critical on the question of dual citizenship: this was largely rejected by Gauthier on the grounds that one citizenship would exclude another, which is not proven for either the Classical or Hellenistic periods. Finally, in relation to dual or multiple citizenship, I question the relevance of the notion of “potential citizenship” used by Gauthier who follows the tradition of Szánto, in relation to the politeia granted on an individual or collective basis: this, in fact, poorly accounts for the actual use of the privileges it contained.